Comparative analysis of the dissociation rate of tetrapyrrole compounds from inclusion complexes with monomeric and polymeric cyclodextrin derivatives - Kablov, Ivan V.; Kravchenko, Irina E.; Zorina, Tatiana E.; Kaskeh, Vahab; Zorin, Vladimir P. (Journal of the Belarusian State University. Physics, 2024)
A systematic study of the formation efficiency and dissociation rate of inclusion complexes of the tetrapyrrole photosensitiser meta-tetra(hydroxyphenyl)chlorine (mTHPC) with monomeric methyl-β-cyclodextrin (M-β-CD) and polymeric derivatives of cyclodextrin – β-cyclodextrin polymer (β-CDPS) and carboxymethyl-β-cyclodextrin polymer (CM-β-CDPS) was carried out using fluorescence methods. It is shown that a number of parameters of fluorescence excitation and emission spectra can be used to control the binding processes of photosensitiser molecules to the studied nanostructures. On the basis of the analysis of binding isotherms, the conclusion about the influence of the structure features of polymers on their interaction with mTHPC was made. The binding constants of mTHPC to β-CDPS and СM-β-CDPS were shown to be significantly higher compared the binding constant of mTHPC to M-β-CD. The study of dissociation processes of mTHPC from inclusion complexes during dilution of solutions, as well as during redistribution of photosensitiser molecules on lipid vesicles showed that the dissociation rate of mTHPC from inclusion complexes with β-CDPS and CM-β-CDPS is significantly lower than the dissociation rate of its from inclusion complexes with M-β-CD. The introduction of photosensitisers as part of inclusion complexes with polymeric cyclodextrins may provide a greater degree of control over the distribution of the drugs, as well as the ability to predict pharmacokinetic behaviour of pigment.
Keywords: temoporfin; photosensitiser; inclusion complexes; cyclodextrins; polymers; lipid vesicles